A bHLH transcription activator regulates defense signaling by nucleo‐cytosolic trafficking in rice. Issue 10 (13th April 2020) - Meng, Fanwei; Yang, Chao; Cao, Jidong; Chen, Huan; Pang, Jinhuan; Zhao, Qiqi; Wang, Zongyi; Qing Fu, Zheng; Liu, Jun
Abstract: Crosstalk between plant hormone signaling pathways is vital for controlling the immune response during pathogen invasion. Salicylic acid (SA) and jasmonic acid (JA) often play important but antagonistic roles in the immune responses of higher plants. Here, we identify a basic helix‐loop‐helix transcription activator, OsbHLH6, which confers disease resistance in rice by regulating SA and JA signaling via nucleo‐cytosolic trafficking in rice ( Oryza sativa ). OsbHLH6 expression was upregulated during Magnaporthe oryzae infection. Transgenic rice plants overexpressing OsbHLH6 display increased JA responsive gene expression and enhanced disease susceptibility to the pathogen. Nucleus‐localized OsbHLH6 activates JA signaling and suppresses SA signaling; however, the SA regulator OsNPR1 (Nonexpressor of PR genes 1) sequesters OsbHLH6 in the cytosol to alleviate its effect. Our data suggest that OsbHLH6 controls disease resistance by dynamically regulating SA and JA signaling. Abstract : Phytohormones play essential roles in plant immunity. In this study, a bHLH transcription activator OsHLH6 was found to dynamically modulate jasmonic acid and salicylic acid signaling by nucleo‐cytoplasm trafficking to defend against rice blast disease.